Pengaruh variasi campuran Eco Racing terhadap performa, konsumsi bahan bakar, dan emisi gas buang pada sepeda motor GL MAX - Andre Muhamad Herbiansyah; Fadelan Fadelan; Kuntang Winangun (Universitas Muhammadiyah Metro, 2022)
The need for motorized vehicles in Indonesia has increased, following the conditions of the Indonesian people who have high mobility. Currently, the Government of Indonesia is trying to control the use of fuel oil, so a solution is needed to modify the octane value of the fuel used while still paying attention to performance and exhaust emissions from vehicles. The addition of Eco Racing to pertalite can increase the octane value, thus affecting fuel consumption. This study aims to determine the effect of Eco Racing variations on performance, fuel consumption, and exhaust emissions on a GL Max motorcycle. This study uses an experimental method with testing using a dynamometer and a gas analyzer. The results showed that the variation of Eco Racing had an effect on performance, fuel consumption, and exhaust emissions on the Gl Max motorcycle with the best mixture being 2 Eco Racing tablets. Performance has increased with the best torque produced being 9.15 Nm and the best power produced is 9.8 HP. Fuel consumption is decreasing until it reaches a value of 2.1 kg/kWh, making it more fuel efficient. Exhaust emissions are more environmentally friendly where CO becomes 5.91%, HC becomes 6011 ppm, and CO2 becomes 2.63%, while O2 increases to 11.51%. The condition of the vehicle affects performance so that the increase in torque and power can only be maintained up to 8000 rpm and the Eco Racing mixture is not able to reduce Hydrocarbon emissions to below the Threshold Value. Where in this study, hydrocarbons were only able to be reduced to 6011 ppm, while the threshold value that had been set was 2400 ppm.